Insecticidal activity of neem oil against Gyropsylla spegazziniana (Hemiptera: Psyllidae) nymphs on Paraguay tea seedlings - Formentini,M. A. (2016)
Abstract Gyropsylla spegazziniana (Paraguay tea ampul) is one of the most important pests of Paraguay tea plants, and prohibition of synthetic insecticide use for control of this pest has led to the search for alternative methods. This laboratory study aimed to compare different control strategies for G. spegazziniana, utilizing a commercial neem seed oil product. Paraguay tea seedlings were treated with neem oil solution both pre- and post-infestation with 5th instar nymphs. The systemic action of neem oil was also evaluated by treating plant soil with the neem oil solution, followed by transfer of the insects to plants 24 h post-treatment. Spray treatments were effective against the pest, especially post-infestation (80% mortality), demonstrating the potential of neem oil for control of the Paraguay tea ampul. No significant effects were observed with respect to systemic activity.